Ideen und Interessen. Zum Verhältnis von Religion und wirtschaftlicher Entwicklung - Deutschmann, Christoph (Ideas and interests. On religion and economic development, 2013)
While concentrating on the rise of modern capitalism, Weber’s seminal studies have little to say about the impact of religions on contemporary economic development. The paper comments about recent approaches to find an answer to the questions Weber left open. If one disregards a priori constructions of culturalist and rational-choice-theories, these approaches end up again in restating the circular relationship between ideas and interests showed already by Weber, albeit clearly with a higher emphasis on interests. However, the author argues that it would be premature to interpret this result simply as a confirmation of Weber’s “disenchantment” thesis. Rather, it goes back to the transformation of the economy itself into an entity that preaches “values”, proclaims “visions” and in this sense develops an affinity to religious movements. The author deepens this view by referring to Marx’ and Polanyi’s interpretation of capitalism as a system of disembedded markets. The disembedding of markets gives rise to a historically new potential of social uncertainty which the actors need to cope with, thereby developing symbolisms showing striking affinities with religious forms. Nevertheless, the analogies between capitalism and religion are limited. (English)
Keywords: Entgrenzung; Institutionen; Kontingenz; Märkte; Säkularisierung; WEBER, Max, 1864-1920; Werte; capitalism; capitalism - religious aspects; consumption (economics); contingency; disembedding; economic aspects; economic development; institutions; markets; philosophy; religion; religion and sociology; religious aspects; secularization; values

The Mystery of Capital or the Mystification of Capital? - Obeng-Odoom, Franklin (Review of Social Economy, 2013)
In contemporary political economic analyses of development processes, Hernando De Soto'sThe Mystery of Capital, has been one of the most discussed, albeit controversial, books. Although well received by global development agencies such as the World Bank, a key exponent of De Soto's work, positing that the creation and institutionalisation of individual property in housing and land revives “dead capital” and creates the conditions that will enable the poor to emerge from abject poverty, has been widely criticised. These criticisms show that (1) the thesis is flawed, (2) the flaw is due to implementational problems and (3) the practical implications arising from the thesis are largely neutral and will neither improve nor worsen poverty. Although agreeing with the first criticism, this paper argues that the second critique must be nuanced, and the third is entirely mistaken. Utilising insights from Joseph Schumpeter, Karl Polanyi and Henry George, it makes the case that applying De Soto's ideas through policy would be ineffective in curbing urban poverty, and actually serve to simultaneously entrench and augment it. Moreover, while finding that De Soto's assumption that the poor possess some economic agency is sound and may, indeed, secure socially beneficial outcomes through pursuing innovative and entrepreneurial endeavours, De Soto's conception of such processes remains largely emasculated from broader political economic considerations.
Keywords: dead capital; economic research; fictitious commodities; fictitious commodity; political economic analysis; poverty; progress amid poverty; property; social innovation

Indigenous Development and the Cultural Captivity of Entrepreneurship - Peredo, Ana María; McLean, Murdith (Business & Society, 2013)
This article argues that thinking about entrepreneurship as a potential instrument for relief from endemic poverty and disadvantage, especially among the Indigenous, has all too often been captive to a concept of entrepreneurship that is built out of constrained economic and cultural assumptions. The authors develop this argument from a critical discussion of contributions by Karl Polanyi and Robert Heilbroner. The result is that approaches to venture have been encouraged that are sometimes a poor fit for the circumstances of those they are meant to benefit, and other forms that could have considerable promise have gone unexplored. This article outlines some features of Indigenous culture and build on the analysis of David Harper to construct an improved notion of entrepreneurship that allows for these distinctive features. The article concludes that research and policy making concerning entrepreneurship as an instrument of development among the Indigenous need to be undertaken with this reconstructed understanding of entrepreneurship that is a better fit for the realities of Indigenous culture.
Keywords: HEILBRONER, Robert; Indigenous development; Indigenous peoples; POLANYI, Karl, 1886-1964; cultural diversity; entrepreneurship; entrepreneurship and culture; poverty

Transforming Capitalism: The Triple Crisis - Kirby, Peadar (Irish Journal of Sociology, 2013)
This article identifies a triple crisis of capitalism based on the three fictitious commodities as identified by Karl Polanyi: labour, money and land. This framework is used to integrate the environmental crisis into the wider crisis of capitalism. It argues that international actions required to reduce greenhouse gas emissions are going to present major challenges for capitalism with implications for the current dominance of market power and the subservience of state and social power. The article critically examines the potential of climate capitalism to achieve a low-carbon society by 2050 and introduces the need to face the challenges of degrowth.
Keywords: climate capitalism; climate change; de-growth; degrowth; development models; fictitious commodities; sustainability

The political economy of public sector trade union militancy under Keynesianism: The case of local government - Gill-McLure, Whyeda (Capital & Class, 2013)
Public service labour’s distinctiveness is insufficiently understood or recognised; and in its ad hoc growth under liberal ideologies of state intervention (those of Mill and Keynes), it has been treated both as if it were and were not public service labour. This paper teases out some of the crucial links between liberal ideologies of state intervention and the social praxis of public service unionism, outlining the latter’s historical struggle against this paradoxical treatment, which culminated in 1970s militancy. The paper supports this argument with a Marxist analysis of public sector labour, drawing on Polanyi’s ‘double-movement’ to understand the limitations of liberal ideologies of state intervention.
Keywords: Marxist analysis; civil service; distinctiveness of public service labour; double movement; ideology; labor process; labour process; liberalism; political economy; public sector union militancy

Capitalism: restless and unbounded? Some neo-Polanyian and Schumpeterian reflections - Harvey, Mark; McMeekin, Andrew (Economics of Innovation & New Technology, 2013)
This paper first explores the notion that the limitlessness of knowledge is a privileged source of the restlessness of capitalism [Metcalfe, J. S. 2001. “Institutions and Progress.”Industrial and Corporate Change10 (3): 561–586; 2002. “Knowledge of Growth and Growth of Knowledge.”Journal of Evolutionary Economics12 (1): 3–13; 2004. “The Entrepreneur and the Style of Modern Economies.”Journal of Evolutionary Economics14 (2): 157–175; 2010. “University and Business Relations: Connecting the Knowledge Economy.”Minerva48 (1): 5–33] when combined with incentives of entrepreneurialism in a market society. Metcalfe gives a central paradigm of evolutionary economics a distinctive turn, with knowledge the pre-eminent source of variation, and markets the primary arena of selection. The paper engages this approach with a neo-Polanyian approach of ‘instituted economic process’, in which the variation and selection dynamic is itself seen as instituted within a particular historical economic context. The paper develops a critique of the evolutionary paradigm firstly by suggesting variations in instituted ‘economies of knowledge’ within a multi-modal conception of capitalism. Further breaking with the bipolar variation-selection paradigm, the paper argues that there has been a significant role of the state as a distinctive source of variation and selection in innovation and economic transformation. This leads us finally to analyse the shifting place of economy in society and polity, and the strategic responses in the USA, Brazil and Europe to the historically novel conjuncture of peak oil and global climate change, as a further source of variation. We conclude that a choice between evolutionary and historical approaches to innovation and economic transformation is a false one, once a universalising and unbounded paradigm of variation and selection is abandoned.
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; economic development; entrepreneurship; evolution; evolutionary economics; instituted economic process; mixed economy; multi-modality; organizational change; variation and selection

Polanyi in the Pilbara - Peck, Jamie (Australian Geographer, 2013)
This paper outlines a ‘substantivist’ approach to the regional economy of the Pilbara in Western Australia, inspired by a constructive reinterpretation of Karl Polanyi's methodological legacy. Beyond the metaphor of embeddedness, it makes the case for a more wide-ranging methodological engagement with Polanyi's brand of substantivist socioeconomics, in dialogue with the empirical investigation of actually existing and variegated socioeconomic formations. A Polanyian optic, amongst other things, calls attention to enduring sources of heterogeneity in this distinctive regional-economic formation, even under the hegemonies extractive capitalism and neoliberal developmentalism.
Keywords: Aboriginal economies; economic geography; mining; the Pilbara

Union Campaigns as Countermovements: Mobilizing Immigrant Workers in France and the United Kingdom - Tapia, Maite; Turner, Lowell (British Journal of Industrial Relations, 2013)
In this article, we compare recent innovative union campaigns: the ‘sans papiers’ campaign in France and the ‘Justice for Cleaners’ campaign in the United Kingdom, both based on a sustained grass-roots mobilization of immigrant workers. Rather than focusing on the ‘usual suspect’ explanatory factors, such as contrasting national settings, union power structures or traditions, our cross-national comparison highlights important underlying similarities in unions' strategic responses to a growing precarious immigrant workforce. In the absence of established channels of representation, both unions decided to act like social movements fighting for social protection. Using Polanyi's framework, we view both case studies as examples of countermovements against heightened levels of global liberalization and precarious employment.
Keywords: comparative labour; countermovement; human resources; international labour; unions

Housing Projects for Low-Income Groups and Modes of Economic Integration: A Comparative Study in Greater Cairo - Abouelmagd, Doaa; Kesteloot, Christian; Corijn, Eric (Tijdschrift voor Economische en Sociale Geografie (Journal of Economic & Social Geography), 2013)
The housing of low-income groups in Greater Cairo has always been difficult. However, the general shortage in housing supply is contrasting with the low occupancy rate of newly constructed public housing units. In contrast, despite their bad living conditions, informal settlements have a high occupancy rate. In order to analyse the reasons behind this contradiction, the paper compares four neighbourhoods ranging from formal and semi-informal to informal housing production and including one rehabilitation project. The livelihood conditions in each settlement are unravelled with the concept of modes of economic integration from Polanyi. For this purpose, semi-structured interviews were conducted and analysed with correspondence analysis. The findings indicate a preference among low-income groups for informal settlements because of three reasons: the advantages of geographical location, the nature of social networks and the strength of private redistribution systems, thus enabling an easier access to means of existence. The results and recommendations are further discussed in the paper.
Keywords: Egypt; Greater Cairo; housing rehabilitation; informal settlements; livelihood; living conditions; low-income housing; modes of economic integration; occupancy rates; poor people; public housing; redistribution; squatter settlements

The Politics of Dispossession: Theorizing India’s “Land Wars” - Levien, Michael (Politics & Society, 2013)
While struggles over land dispossession have recently proliferated across the developing world and become particularly significant in India, this paper argues that existing theories of political agency do not capture the specificity of the politics of dispossession. Based on two years of ethnographic research on anti-dispossession movements across rural India, the paper argues that the dispossession of land creates a specific kind of politics, distinct not just from labor politics, but also from various other forms of peasant politics that have been theorized in the social sciences. It illustrates how the process of land dispossession itself shapes the targets, strategy and tactics, organization, social composition, goals, and ideologies of anti-dispossession struggles. It concludes with reflections on why land conflicts are less easily institutionalized than labor conflicts and may therefore constitute a significantly disruptive force in the emerging centers of global capitalism for the foreseeable future.
Keywords: India; accumulation by dispossession; agrarian change; agriculture; capitalism; eviction; land grabs; peasant politics; peasants; property rights; social movements

Responding to the crisis: food co-operatives and the solidarity economy in Greece - Rakopoulos, Theodoros (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
This article discusses a case of popular social response to imposed austerity and recession in Greece. It focuses on the anti-middleman movement in an Athens suburb. It also addresses the broader picture of the current Greek crisis, explaining how participants in this grassroots response extend their activity beyond food distribution, beginning to imagine modes of economic conduct and interaction different from those currently dominant in Greece. I explore their efforts to turn the food market they have established in Athens into a formal co-operative which links consumers in their neighbourhood directly to selected farmers through bonds of solidarity, and to work with others to create a network of similar co-operatives which will span the whole country. I argue that their endeavours strongly resemble the co-operativism and practical socialism advocated by important social theorists such as Mauss and Polanyi, and suggest that it may be important for the young activists in Athens to learn more about their ideas.
Keywords: Greece; Greek crisis; MAUSS, Marcel, 1872-1950; anthropological research; anti-middleman movements; economic development; financial crises; financial crisis; food co-operatives; food industry; horizontal co-operative networks; recessions; solidarity economy; sovereign debt crisis

Towards a human economy: reflections on a new project - Sharp, John (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
The University of Pretoria's Human Economy project began at the end of 2010. To date it has involved eighteen post-doctoral fellows, drawn from around the world, and eight doctoral candidates, all from Africa. This paper reviews the project's progress, drawing attention to how its participants have come to construe the notion of a 'human economy' and the main social theorists on whom they have drawn in doing so. The development of our thinking regarding a human economy is explained by reference to the two edited volumes, comprising contributions from all the post-doctoral fellows, which will be published in the near future. Challenges for future research are considered in the final part of the paper.
Keywords: MAUSS, Marcel, 1872-1950; South Africa; University of Pretoria; doctoral degree; economic development; human economy; market exchange; mutuality; plural economy; reform; revolution; social development; social sciences

Cosmologies and Regionalisms from ‘Above’ and ‘Below’ in the post-cold war Americas: the Relevance of Karl Polanyi for the 21st century - Roncallo, Alejandra (Third World Quarterly, 2013)
Drawing on a Polanyian analysis of the land question, this article aims to analyse both Western and Indigenous cosmologies of Abya Yala—the name that indigenous peoples give to the American continent—to understand the relationship between human beings and land and nature. These cosmologies are at the heart of the way in which two distinct societies construct their regional space, one from ‘above’, the other from ‘below’, and they are therefore key to understanding today’s climate change problématique. Following this nexus it is argued that, since the end of the Cold War, a new regional ‘double-movement’, unleashed by the quest for land and natural resources has been in the making. This is a superstructural or legal battle between Western transnational regime-making and a law that originated at the ‘centre of the Earth’. The article explains both regionalisms and the dialectical interaction between them and demonstrates that Karl Polanyi’s legacy remains relevant for the 21st century.
Keywords: climate change; cosmologies; double movement; indigenous land question

Polanyi in an Hourglass: The Two Lives of a Sociological Classic - Frerichs, Sabine (Studies in Law, Politics & Society, 2013)
This article aims to show that studies of transnational risk regulation can benefit from Polanyian and neo-Polanyian research agendas in the field of law, economy, and society. Risk regulation would then be under-stood as a corrective force within the market society. Drawing on the relevant literature in the field, Karl Polanyi's work is contextualized both in the past ("scholarship before and beside Polanyi") and in the present ("scholarship after and beyond Polanyi"). The review considers developments within sociology, its neighboring disciplines economics and jurisprudence, and the interdisciplinary research fields of "economy and society," "law and society," and "law and economy." The article demon-strates that Polanyi is a "late classic" who shares the holistic orientation of classical historical scholarship. At the same time, it is argued that his "early revival" is due to the topicality of his criticism of the market society, and its inherent risks, in an era of neoliberalism and globaliza-tion. By going back and forth in time, the article situates Polanyi in a line of holistically minded scholarship that combines insights of general, economic, and legal sociology in what can be called the "economic sociol-ogy of law." This is "old" and "new," at the same time.
Keywords: classical sociology; contemporary sociology; economic sociology; economic sociology of law; general review; interdisciplanary research; law and economics; market society; neoliberalism; risk regulation; sociological research

After a Romantic Aspiration to Society: Harnessing the Regulatory Capacity of a Social Sphere - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This introduction unpacks the key question that informs the articles in this special issue. How does a social sphere inform regulation and, more specifically, how can the regulatory capacity of a social sphere be har-nessed, as an alternative or significant complementary force to state reg-ulation and reliance on the self-regulatory capacity of markets? This question is salient and topical also in light of the search for new regula-tory strategies and perspectives in the aftermath of the 2007 financial and subsequent EU sovereign debt crises, which have led to a major rea-lignment of economy and society in a number of countries. This introduction argues that economic sociology is a crucial reference point for understanding more about the social practices that constitute business behavior. It enables to explore the scope and significance of often interlinked social and legal norms for regulating various transna-tional risks that economic activity can give rise to. The introduction therefore locates the quest for understanding more about the regulatory capacity of a social sphere in debates that draw on Karl Polanyi's analy-sis of the embedding, disembedding, and re-embedding of economic activ-ity into social norms. The introduction highlights one of the key themes developed in this special issue, the idea of society within economy which questions an assumed conceptual distinction between economy and society. This introduction concludes by specifying how the accounts of risk regu-lation developed in this special issue chart a path that is different from recent explorations of the role of a social sphere in regulation, which were conducted under the banner of "the sociological citizen," "regula-tory sociability," and "collaborative governance."
Keywords: European Sovereign Debt Crisis, 2009-; European Union; crisis; economic sociology; economic sociology of law; financial crisis; international business enterprises; regulation; social sphere; socio-legal studies; state regulation; transnational risk

From Polanyi to Discourse Theory - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This article starts from the assumption that economic sociology, including Karl Polanyi's work, can contribute fresh perspectives to regulation debates because it opens up new understandings of the nature of economic activity, a key target of legal regulation. In particular this article examines Polanyi's idea that society drives regulation. For Polanyi the "regulatory counter-movement" is society's response to the disembedding -- in particular through the proliferation of markets -- of economic out of social relationships. Section One of the article identifies three key chal-lenges that arise from this Polanyian take on regulation for contempor-ary regulation researchers. First, Polanyi focuses on social norms restraining business behavior, but neglects social norms embedded in law as also shaping regulation. Second, he seems to imply a clear-cut concep-tual distinction between "economy" and "society." Third, his analysis sidelines the role of interest politics in the development of regulation. Addressing the first of these three key challenges, Section Two of this article therefore argues that a Polanyian vision of "socialized" legal reg-ulation should build on contemporary accounts of responsive law and reg-ulation, which focus attention on social norms informing legal regulation. Section Three of this article tackles the second key challenge raised by Polanyi's work for contemporary regulation researchers, that is, how to transcend a modernist perspective of "economy" and "society" as clearly demarcated, distinct fields of social action. It argues that discourse the-ory is an important alternative theoretical resource. Drawing on Laclau and Mouffe, the article suggests that understanding "economy" and "society" as performed by open and relationally constructed discourses helps to capture interconnections between "economy" and "society" that become particularly visible when we analyze how specific regulatory regimes work at a medium- and small-scale level. These points are further brought to life in Section Four through a discussion of the European Union (EU) regulatory regime for trade in risky, transgenic agricultural products, and in particular the current reform debates about the consideration of the "socioeconomic impacts" of such products.
Keywords: European Union; European Union regulation; discourse theory; economic sociology; embeddedness; embedding theorems; responsive regulation; socio-economic impacts; socioeconomics; transgenic agricultural products

A Systems Theory Perspective on Polanyi's Great Transformation: The Case of Financial Derivative Contracts - Paterson, John (Studies in Law, Politics & Society, 2013)
Whereas much of the renewed interest in Polanyi's Great Transform-ation speculates that the rebalancing of economy and society he foresaw might now be emerging in the context of the financial crisis, the systems theory perspective adopted in this article concludes that there are good reasons to believe that such a shift may be no closer. From an examina-tion of credit default swaps and corporate bonds, the article suggests that finance may best be understood as an internally differentiated subsystem of the economy and thus perhaps peculiarly proof against efforts to exert control over it. Concluding that Polanyi's analysis lacks the conceptual tools to cope with contemporary conditions when compared to systems theory, the article nevertheless suggests that his approach may usefully be extended by adding a fourth fictitious commodity - risk -- to the familiar trio of land, labor, and money.
Keywords: POLANYI, Karl, 1886-1964; contracts; corporate bonds; derivatives; economic aspects; economic sociology; economy; markets; prices; society; swaps (finance); systems theory

Trust and Regulation: Insights from the Mining Industry - Schiavi, Petrina (Studies in Law, Politics & Society, 2013)
This article develops Polanyi's (2001) theme of harnessing the regula-tory capacity of a social sphere by focusing on trust as an emotion for framing risk regulatory regimes. Using the global mining sector as its focus, it explores the role of trust in the regulation and corporate man-agement of social and environmental risk Sociological perspectives on trust are employed to identify and analyze dynamics of trust in the mining industry. The article draws on data col-lected between 2004 and 2008 by way of participant observation, docu-ment analysis, and in-depth qualitative interviews with around 40 representatives of the mining industry, NGOs, and regulators. Trust-rela-tionships are an example of harnessing the regulatory capacity of a social sphere, but they can also undermine regulatory effort where trust is abused. The effectiveness of trust-based regulation would be enhanced by sanctions for nonperformance that target corporate motivations and financial performance. This research focused on a selection of large, multinational mining corporations with a presence in Australia. Generalizations could not be made from this research about smaller mining entities or single-country or state-owned corporations. A better understanding of corporate trust-building behaviors and motiva-tions can help inform more effective regulatory strategy for improving corporate, social, and environmental impacts. This article contributes to the body of knowledge about the regulation of the social and environmen-tal performance of the mining industry. This is important as many of the remaining accessible mineral deposits across the globe are in areas of environmental and social significance.
Keywords: POLANYI, Karl, 1886-1964; corporate responsibility; delegated legislation; environmental risk assessment; financial risk; mineral industries; mining industry; regulation; risk; social responsibility of business; trust

Sovereign Debt Restructuring in the Eurozone: A Polanyian Reading of Private Law Enforcement - Thomas, Dania (Studies in Law, Politics & Society, 2013)
The social protests ort the streets of indebted sovereigns in crises across the Eurozone have made debt restructuring an imperative. Further delay in achieving this expeditiously and equitably significantly exacerbates the social costs of crises from which current and future generations will struggle to recover. This article examines the feasibility of the drastic and widespread debt restructuring needed to resolve the problem in the face of existing private law sanctions that protect individual creditor rights. It relies on an analysis of US policy in the transition to a securi-tized market and of key sovereign debt cases to reveal the historical con-tingency of private law protections. It concludes by showing that the effectiveness of private law protections have always been constrained by the overriding imperative to achieve debt sustainability with negotiated and consensual workouts. This can be achieved in the Eurozone with stat-utory constraints on enforcement action pending the settlement of debt workouts as suggested in a recent proposal.
Keywords: European Sovereign Debt Crisis, 2009-; Eurozone crisis; Eurozone debt crisis; POLANYI, Karl, 1886-1964; US debt litigation; civil law; contingency theory (management); international finance; private law enforcement; securitization; sovereign bond contracts; sustainability

"Etiquette and Magic": Between Embedding and Embedded Corporate Social Responsibility - Voiculescu, Aurora (Studies in Law, Politics & Society, 2013)
This article looks at corporate social responsibility (CSR) as a discur-sive social practice that attempts to interrogate the global market econ-omy and its neoliberal underpinnings and that reflects as well as frames and shapes domestic and global politics and institutions. Drawing upon Karl Polanyi's notions of reciprocity and redistribution while also emphasizing the normative content of the concept, the article inquires into the position that the CSR discourse occupies in addressing the cor-porate transnational risks derived from social tensions and conflicts and more generally, in answering social expectations for justice. The Polanyian perspective highlights the CSR discursive quest for a missing conceptual consistency and implicitly, for a constructive "critical" core. From this perspective, the article shows CSR to reside within controver-sial conceptual boundaries; a discursive social practice that engages with the social aspiration of embedding market economy in society while it is also in need of reclaiming its critical core and its potential for social change.
Keywords: civil economy; corporate social responsibility; embedding theorems; neoliberalism; reciprocity (commerce); reciprocity and redistribution; social change; social embeddedness; social responsibility of business; socio-legal studies

How Markets Work: The Lawyer's Version - Weidemaier, W. Mark C.; Gulati, Mitu (Studies in Law, Politics & Society, 2013)
This article combines two sources of data to shed light on the nature of transactional legal work. The first consists of stories about contracts that circulate among elite transactional lawyers. The stories portray law-yers as ineffective market actors who are uninterested in designing super-ior contracts, who follow rather than lead industry standards, and who depend on governments and other outside actors to spur innovation and correct mistakes. We juxtapose these stories against a dataset of sover-eign bond contracts produced by these same lawyers. While the stories suggest that lawyers do not compete or design innovative contracts, their contracts suggest the contrary. The contracts, in fact, are consistent with a market narrative in which lawyers engage in substantial innovation despite constraints inherent in sovereign debt legal work. Why would lawyers favor stories that paint them in a negative light and deny them a potent role as market actors? We conclude with some conjectures as to why this might be so.
Keywords: POLANYI, Karl, 1886-1964; contracts; international finance; lawyers; lead industry; socioeconomics; sovereign debt; transactional marketing

Polanyi's Magnum Opus ? Assessing the Application of the Counter-Movement in International Political Economy - Worth, Owen (International History Review, 2013)
The concept of the ‘counter-movement’ has had a significant impact within studies in International Political Economy (IPE). In the light of the credit crisis and the growth of growing resentment to the notion of the free market, the idea of the counter-movement has been utilised to understand social reaction to neoliberalism. This article argues that whilst the counter-movement has been used in unique and innovated ways, Karl Polanyi himself used the term largely to refer to a specific period in nineteenth-century British history. This article argues that whilst the counter-movement remains interesting, its application remains open to scrutiny. It questions whether the concept was indeed central to Polanyian economic thought and how much can be given to it in today's contemporary era of neoliberalism. It also suggests that by focusing merely on the counter-movement, Polanyian accounts within IPE are in danger of ignoring much of his wider critique of market economics.
Keywords: capitalism; countermovement; economic policy; equilibrium (economics); foreign investments; free enterprise; international economic relations; international political economy; neoliberalism

Is Environmental Management Really More Collaborative? A Comparative Analysis of Putative ‘Paradigm Shifts’ in Europe, Australia, and the United States - Benson, David; Jordan, Andrew; Smith, Laurence (Environment and Planning A, 2013)
It is a truism that environmental management has experienced a significant change in the locus of governing, in which centralised forms of steering have been gradually replaced by more collaborative management approaches organised at the ecosystem scale. Whereas much research capital has been expended on informing their design and promoting their uptake, surprisingly little systematic comparative empirical research exists on the precise nature and extent of what is often described as a ‘paradigm shift’ in governing. We address this gap by examining how one issue often deemed to require deeper ‘collaboration’, namely, catchment management, has been addressed in three comparable federal political systems: the European Union; the USA; and Australia. On the basis of a fresh and more comparable account of the forms and modalities of collaboration, we reveal that, although collaboration has undoubtedly grown in recent decades, its depth and extent remains highly variable both across and within the three cases. We also examine what these subtly different geographical ‘contours of collaboration’ imply for future research and practice.
Keywords: catchment management; central control; collaboration; environmental science; federalism; governance; neoliberalism; paradigm shift

From Neoliberalism to Pluralism: A Response to Mulheirn and Jacobs - Finlayson, Alan (The Political Quarterly, 2013)
This essay puts into context the debate between Michael Jacobs and Ian Mulheirn, exploring the theories and themes underpinning their arguments, published in issue 84 1 of the Political Quarterly. It discusses, firstly, the roots of Mulheirn's approach in European neoliberalism and, secondly, the roots of Jacobs' approach in a range of sources currently contending for authority over debates within the Labour party. These include themes drawn, broadly, from Polanyi, Keynes, Schumpeter and Schumacher. In a conclusion the article makes the case for a ‘pluralistic’ to the organisation of political and economic power in the UK.
Keywords: neoliberalism; pluralism; political economy; social market

Turning Financial Markets inside Out: Polanyi, Performativity and Disembeddedness - Muellerleile, Chris (Environment and Planning A, 2013)
In light of the spread of markets across the globe and deeper into daily life, this paper argues for a more robust analysis and application of Karl Polanyi's conception of (dis)embedded markets coupled with the performativity thesis authored mainly by Michel Callon. It suggests that while disembeddedness as a concept is necessary for an analysis of contemporary financial markets that are increasingly self-referential, it is not sufficient. Despite the suggestion of a gulf between Polanyian and Callonian economics, there are important similarities in the two frameworks. The similarities are considered along with the considerable difference, all in an attempt to develop a more robust methodological framework for analyzing financial markets. Performativity, it is argued, can help fill the gaps in Polanyi's embeddedness framework, albeit only when that concept's tendency to produce aspatial and apolitical arguments are taken seriously. The paper uses an abbreviated case study of the development of US financial derivative markets in the 1970s and 1980s to argue that markets must be considered in light of both their institutional and geographic entanglements as well as their (dis)embeddedness in systems of calculativeness and mathematical modeling. Specifically the paper analyzes the tension between the derivative origin story authored by Donald MacKenzie, which focuses on neoclassical pricing models like the Black—Scholes—Merton option pricing formula, and my own empirical research, which suggests the urban-economic geography of Chicago played a key role in the development of these instruments.
Keywords: Black—Scholes; CALLON, Michel; Chicago; disembeddedness; economic geography; embeddedness; financial derivatives; markets; performativity; urban geography

Disembedding Polanyi: Exploring Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
The paper provides an introduction to a theme issue devoted to the influence—and the potential—of the work of Karl Polanyi in the field of economic geography. Polanyi has been an inspirational figure in the heterodox field of ‘socioeconomics’, where the inseparability of the economic and the social is taken to be axiomatic. He has also made recurrent appearances in economic geography since the early 1990s, as a progenitor of the ‘networks and embeddedness’ approach and in his role as a prescient critic of market fundamentalism. But the potential of Polanyian approaches in economic geography has only been fitfully explored. In this context, the contributions to this theme issue make the case for a more sustained—but also open, critical, and creative—engagement with Polanyi's legacy.
Keywords: economic geography; embeddedness

For Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
Karl Polanyi has been an influential but also somewhat elusive figure in economic geography. Best known for his evocative notion of social embeddedness, it is perhaps fitting that Polanyi's presence has been more metaphorical than substantive. The paper asks what a more engaged Polanyian economic geography might look like. Focusing on methodological affinities, a response is developed in terms of a commitment to the substantivist (as opposed to formal) analysis of actually existing economic formations, together with a more purposive embrace of institutionalism, holism, and comparativism.
Keywords: comparative economy; economic geography; institutionalism; substantivism

Living without Fruit Flies: Biosecuring Horticulture and its Markets - Phillips, Catherine (Environment and Planning A, 2013)
In this paper, informed by more-than-human and biosecurity literatures, I attend a neglected nonhuman considered a serious agricultural pest: the fruit fly. In addressing what it takes to live without fruit flies, biosecurity is theorised as ongoing, enacted achievement sustained (or not) by everyday and eventful interactions of heterogeneous spaces, strategies, and participants—human and nonhuman. Relations of fruits, flies, and people are explored through one vital attempt to biosecure life: Australia's Fruit Fly Exclusion Zone (FFEZ), a tristate pest-free area established to protect commercial horticulture from the fruit fly. Fruit flies become problematised as their appetites and mobilities confound fruit production and marketing, and affiliated biosecurity controls. Making fruit safe enrolls policy and agricultural sectors, but also more dispersed agents (travellers, residents, trees) and management sites (primarily off-farm). Since its introduction, the FFEZ's ongoing biosecuring normalised, with only occasional outbreak events. However, recent unprecedented outbreaks evoke questions about the FFEZ's future status. In such eventful times, it is worth reflecting on what kinds of living are possible in biosecurity zones—for flies, for resident human communities, and for agrifood networks.
Keywords: Australia; Queensland fruit fly; agriculture; biosecurity; more-than-human

Men and Things: Karl Polanyi, Primitive Accumulation, and Their Relevance to a Radical Green Political Economy - Prudham, Scott (Environment and Planning A, 2013)
Now is an important moment to be thinking and talking about a critical and normative green political economy. Whether via attempts to develop effective and socially just climate policies at multiple scales of governance [including REDD (reducing emissions from deforestation and degradation) schemes], or to develop proliferating and controversial neoliberal instruments for dealing with undesirable environmental change, environmental governance, and environmental change in the context of contemporary global capitalism are on the agenda. What would a critical and normative green political economy for the current moment look like? This paper draws on Karl Polanyi's The Great Transformation as a resource for answering that question. In particular, Polanyi's discussion of problematic and dualistic notions of nature and society in early political economy and the role he accords social struggles over land in developing his theory of fictitious commodities, embeddedness and the double movement are revisited. The paper stresses how Polanyi's ideas, at once conceptual and polemical, draw centrally on Marx's theorization of primitive accumulation as an inherent, ‘extra-economic’ facet of historical—geographical capitalism, a differentiated unity linking the commodification and objectification of human and nonhuman natures as exchange-values. In this respect, Polanyi offers (or seems to offer) a potential reconciliation of a politics of nonhuman and human nature through his emphasis on primitive accumulation as a site of both political struggle and epistemic transformation.
Keywords: Karl Polanyi; economism; green political economy; primitive accumulation

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

Marketization beyond Neoliberalization: A Neo-Polanyian Perspective on China's Transition to a Market Economy - Zhang, Jun (Environment and Planning A, 2013)
This paper proposes a neo-Polanyian framework of neoliberalization-as-marketization for understanding geohistorically embedded marketization based on five interlinked theoretical conceptualizations: embedded marketization, hybrid integration, double movement, active society, and qualitative state. I argue that this framework can be useful to supplement existing theorizing of neoliberalism, and to facilitate comparative case studies across vastly differently contexts. This framework is then taken to analyze China's post-Mao transition to a market economy. I argue that China's gradualist transition from a centrally planned economy to a mixed economy has been maneuvered by a self-regulating party-state (dis)embedded in a deactivated (active) society. Due to the existence of multiple veto players and intraparty ‘double movement’, the marketization was able to be mostly socially progressive until 1993. However, it was no longer the case when the ‘socialist market economy’ was enshrined and, without political liberalization, the Chinese version of neoliberalization has become even bleaker than elsewhere.
Keywords: China; double movement; marketization; neo-Polanyian; neoliberalization

The boundaries of cosmopolitanism: Karl Polanyi and the 'Magyar-Jewish mongrel' - Dale, Gareth (Environment & Planning A, 2013)
The author offers his opinion on Hungarian historian Karl Polanyi and the views Karl expressed in a series of letters he sent to his brother Michael Polanyi. In these letters Karl wrote about the Germans attitude towards other Jews and the developing volatile social environment in Budapest, Hungary at the beginning of the 20th Century. He also wrote on the animosity between the Germans and the Jews.
Keywords: Baltic States; Germans; Jews; POLANYI, Michael, 1891-1976; biography; cosmopolitanism; history; social development

Pi̇yasa: Adam Smith Versus Karl Polanyi̇ - Gökten, Yeliz SARIÖZ (Academic Review of Economics & Administrative Sciences, 2013)
In this study author will try to make comparative analysis of Adam Smith and Karl Polanyi's ideas about market. According to Smith market is a mechanism which allocating resources through invisible hand. Contrary to Smith, Polanyi, asserts that a market is a intervention style to economy. Intervention is an inherent property of market. In the first part of this study Adam Smith's opinions about market which assings limited duty to state and defends social interest will come true through invisible hand will be examined. Second part will concentrate on Karl Polanyi's arguments against appear of market society and market economy. At the end of the study, the author has tried to analyse two different market conceptualization and to assert how well this approaches to understand our times. (English)
Keywords: Piyasa; Piyasa Sistemi; SMITH, Adam, 1723-1790; comparative studies; economic research; economists; market; market system

The Institution, the Economy and the Market: Karl Polanyi's Institutional Thought for Economists - Maucourant, Jerome; Plociniczak, Sebastien (Review of Political Economy, 2013)
This paper aims to clarify the logical structure of Karl Polanyi's concept of institution, especially with regard to his most important contribution to political economy—the conception of self-regulating markets as institutions. Although Polanyi did not provide a well-developed concept of institution, this article argues that such a concept exists in his work. Moreover, there is in Polanyi's work a sophisticated institutionalist account of the self-regulating market that has been largely overlooked as Polanyi does not present it explicitly. Analyzing the economy as an institutionalized process, as Polanyi does, reveals that the market is neither a natural nor a spontaneous phenomenon—a conclusion that runs counter to conventional economic thinking. Polanyi's approach enables us to view capitalism (the ‘market society’ in Polanyi's language) through a highly specific cultural fact: the fiction of the self-regulating market. This institutional perspective needs to be reassessed beyond new-institutionalist theoretical constructions.
Keywords: economic structure; free enterprise; institutions (philosophy); philosophy of economics; social facts

Polanyian pedagogies in planning and economic geography - Rankin, Katharine N. (Environment & Planning A, 2013)
The author offers his opinion on social economic planning and the educational courses available on them. The author states that planning social economy was a part of Hungarian economist Karl Polanyi's policy in early 20th century to stabilize the economic conductions in Hungary at that time. The auditor says that Polanyi's book "the Great transformation" formed the basis. which if acted upon, would have preevented the Global Financial Crisis of 2008.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; central economic planning; global financial crisis, 2008-2009; nonprofit sector

Class and situated knowledge in Polanyi's The Great Transformation - Schoenberger, Erica (Environment & Planning A, 2013)
The author offers his views on a controversial fundraising organized by then U.S. Presidential Candidate Mitt Romney in May 2012 where he commented that he won't be bothered about a section of society who only have access to national income but have not contributions or income tax to give. The author cites this as one the reason why Romney was not successful and states that Hungarian Economists Karl Polanyi's socioeconomics theory is relevant in the 21st century.
Keywords: Great Transformation, The (Book); POLANYI, Karl, 1886-1964; ROMNEY, Mitt, 1947-; income tax; national income; political fundraising; socioeconomics; voters

Polanyi, double movements, and political economic transformations - Smith, Adrian (Environment & Planning A, 2013)
The author offers his opinion on Hungarian Economist Karl Polanyi's opinion on social economy. The auth through use of recent events such as the Arab Uprising since 2011 and the post communism societies discusses Polanyi's views with those of political economic planners. The author states that social change within a society post the economic recession could have been avoided had Polanyi's views being taken seriously.
Keywords: Arab Spring Uprisings, 2011-; Arab countries; POLANYI, Karl, 1886-1964; double movement; history; nonprofit sector; political economic analysis; postcommunist societies; social change

The two Karls, or reflections on Karl Polanyi's The Great Transformation - Walker, Richard (Environment & Planning A, 2013)
The article reviews the book "The Great Transformation," by Karl Polanyi.
Keywords: Great Transformation, The (Book); book review; nonfiction; socioeconomics

Karl Polanyi - Le père de la socioéconomie - Journet, Nicolas (Les Grands Dossiers des Sciences Humaines, 2013)
Penseur au parcours très singulier, Karl Polanyi est l’un des fondateurs d’une discipline nouvelle, l’anthropologie économique, qui se consacre à l’étude des échanges dans les sociétés anciennes et ambitionne de théoriser, à l’échelle de l’humanité, ce qu’il en est des rapports entre société et économie.?Pourtant, son œuvre la plus célèbre, La Grande Transformation, ne sort pas du cadre de l’histoire... Plan of the article: Radical liberalism versus social life The free market: an intolerant doctrine An argument against neoclassical orthodoxy
Keywords: free market; neoclassical economics; radical liberalism

'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

Rudderless in a Sea of Yellow: The European Political Economy Impasse for Renewable Transport Energy - Harvey, Mark; Pilgrim, Sarah (New Political Economy, 2013)
Faced with the twin challenges of anthropogenic climate change and ‘peak oil’, the need for an urgent and radical transformation of transport energy has been widely recognised. Adopting a neo-Polanyian economic sociology approach, this article asks what conditions European governance capacity to respond to these challenges, at either national or regional levels, using biofuels as a case study. It asks if the complexity of its political institutions, and the heterogeneity of interests and economic organisations, present ‘the biggest obstacle of all’ (Cohen 2007) to reduce fossil fuel dependency. By examining the European Commission level and comparing five countries, evidence is produced for a political failure in terms of continued fossil fuel dependency. Incumbent interests in the agricultural sector and a distinctively European legacy of a transport fleet dependent on fossil diesel, have led to a marriage of convenience between rapeseed farmers and vehicle manufacturers. As a consequence, rather than escaping from the path dependency on fossil fuels (Unruh 2000), Europe has gone down a cul-de-sac of rapeseed biodiesel inherently limited in scope, and with the low levels of greenhouse gas emissions savings. Ironically this outcome is in part an unintended consequence of opposition to biofuels from environmentalist groups and politics.
Keywords: agriculture; biodiesel fuels; biofuels; biomass energy research; climate change; climate change research; economics; peak oil; politically instituted markets; rapeseed

Interests, Resources and Status: The Distribution of Income, Work and Authority in the Family in a Northern Hungarian Village - Sárkány, Mihály (Acta Ethnographica Hungarica, 2013)
The author deals with two interconnected features of contemporary Hungarian rural family life from a historical perspective based on fieldwork carried out in Varsány in the early 1970s and between 2000 and 2005. The first is the intertwining of the lives of successive generations of families in a period when other segments of Hungarian society were becoming more individualistic. This case puts into question whether economic models of the direction of the flow of goods between generations (linear, altruistic or exchange models) are applicable for this situation. The author suggests that Polányi's ideas may be of help in understanding this phenomenon. The second is the balance of genders within families. Tatjana Thelen, who did fieldwork in another Hungarian village, Mesterszállás, pointed out a decline in the status of women. She holds the Hungarian policy of privatisation and reprivatisation responsible for it, which followed the great socio-economic and political change from socialism to capitalism in 1990. As a similar decrease in the status of women did not occur in Varsány, the author argues that other factors also should be taken into consideration for analysing such situations, like the role of commuting, education, and women's share in landed property.
Keywords: Hungary; authority; distribution (economic theory); families; gender; generation; income distribution; research; rural family; transfer of income; work

Le rendement et le butin. Regard écologique sur l'histoire du capitalisme, The Yield and the Booty. An Ecological Perspective on the History of Capitalism - Charbonnier, Pierre (Actuel Marx, 2013)
This article examines the history of globalized capitalism from the perspective of the relations to the environment which it helped to construct. It proposes a definition of globalized capitalism as a form of relation to nature. If philosophy has frequently postulated that modernity is characterized by the dissociation between the natural and the social, the history of the economic take-off of the states of Western Europe throws a singular light on this hypothesis. Combining a reading of Karl Polanyi and Kenneth Pomeranz, it can be argued that the logic of commodity always tends to render invisible the relations to the environment which define capitalism. The temporal and spatial lag between those populations which live the concrete experience of the industrial revolution and the enormous natural resources required for its appearance enable us to understand how it has been possible for the representation of the economy to become so radically dissociated from its natural metabolism.
Keywords: globalized capitalism; nature and society; political thought

Unravelling the Embedded Liberal Bargain: Labour and Social Welfare Law in the Context of EU Market Integration - Ashiagbor, Diamond (European Law Journal, 2013)
European economic integration with a minimalist social policy at EU level was in part made possible by strong domestic labour market and social welfare institutions. The main contention of this paper is that EU market liberalisation was embedded within institutions of social citizenship at domestic level, which served to counter the liberalisation of the internal market. But this settlement has been put under strain. In addition to the challenges posed to the sustainability of European welfare states by the global economic crisis, the internal market jurisprudence of the Court of Justice casts doubt on the sustainability of the ‘embedded liberal bargain’. This paper focuses on the role of the Court, in particular in its jurisprudence on the interaction between (EU) market freedoms and (national) labour law, which undermines the ability of states to retain their regulatory autonomy over labour or social welfare law and, arguably, speeds up the unravelling of the ‘embedded liberal bargain’.
Keywords: European Union; embedded liberal bargain; market liberalisation; market liberalization; social citizenship

A variety of capitalism … with Chinese characteristics? - Peck, Jamie; Zhang, Jun (Journal of Economic Geography, 2013)
The ‘varieties of capitalism’ framework represents an influential methodological innovation in the field of comparative political economy. It seeks to account for enduring spatial variations in national economic performance by recourse to macroinstitutional analysis, drawing ideal-type distinctions between liberal market economies, modeled on USA, and coordinated market economies, modeled on Germany. Moving beyond critiques of varieties literature—for instance, its methodological nationalism; its preoccupation with limited, formal registers of (national) institutional variety; its growing reliance on rational-choice, firm-centric methods; its failure to account for the pronounced interpenetration and mutual dependence of capitalist economies and its tendency to privilege typological elaboration over causal explanation—this article explores the critical (counter?) case of Chinese capitalism. It considers the extent to which the Chinese economy can be meaningfully characterized as capitalist; the character of its state form and recent development path and its position within—or beyond—conventional understandings of capitalist variety.
Keywords: China; Chinese capitalism; capitalism; developmental state; economic structure; economic systems; free enterprise; socialist state; variegated capitalism; varieties of capitalism

On Life as a Fictitious Commodity: Cities and the Biopolitics of Late Neoliberalism - Rossi, Ugo (International Journal of Urban & Regional Research, 2013)
Building on a biopolitical understanding of the economic crisis, this essay contends that the occurrence of the crisis warns that life is not a real commodity but - to put it in Karl Polanyi's terms - a 'fictitious commodity'. This means that life cannot be integrally subsumed within the economy, and therefore the crisis is to be seen as a pathological way in which societies react to the pervasiveness of capitalist relations, showing the illusory character of self-regulating markets and ownership ideologies. Two mutually contradictory biopolitical responses to the neoliberal crisis, led by the state and grassroots movements respectively, are discussed in the concluding section of the essay.
Keywords: biopolitics; biopolitics (sociobiology); capitalism; consumers; crisis; fictitious commodities; global financial crisis, 2008-2009; government regulation; home ownership; housing; late neoliberalism; neoliberalism; urban economics

A crise de legitimidade da governança climática global. Combinação de uma perspetiva marxista e polanyiana - Van Vossole, Jonas (2013)
This article frames recent problems of the RIO+20 summit, the failure of the Copenhagen Climate Change Conference (COP15) and the problems of the carbon markets within a broader legitimacy crisis of global governance, consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between the Marx-type of contestation, referring to emerging classes/states, and the Polanyi-type of contestation, referring to the victims of global mercantilization. In the case of climate governance, these winners and losers are represented by BRICS in climate negotiations and by the global environmental justice movement. (English)
Keywords: RIO+20; United Nations Conference on Sustainable Development (2012 : Rio de Janeiro, Brazil); capitalism; capitalisme; capitalismo; carbon dioxide mitigation; environmental aspects; environmental justice; gouvernance; governance; governança; international cooperation; international cooperation on climate change; international cooperation on environmental justice; international cooperation on environmental policy; justice environnementale; justiça ambiental; legitimacy; legitimation (sociology); legitimidade; légitimité

Promoting Freedom of Association in China? Putting Transnational Corporate Social Responsibility into a National Context - Chan, Chris King-Chi (Journal of Comparative Asian Development, 2013)
Using the findings of an intensive case study of a corporate social responsibility (CSR) project in China, this paper argues against the view that CSR and the state's regulations are mutually exclusive. It contests that the theorization of the transnational social movement (TSM) should not ignore the development of the state regime, which in turn is shaped by the power relations in the workplace and the community, and is embedded in the national political history. The findings of this research support the Polanyi-inspired approach which sees CSR as being embedded in the changing patterns of business–government–society relations. This approach highlights that the behaviour of the state and the engagement of civil society have actively shaped the scope and the implementation of CSR. Following this line of argument, this paper provides evidence of the dynamics and paradox of workers' and grassroots NGOs' engagement in CSR in China. The specificity of China stems from the state, on the road of China's transition from a state socialist country to being a part of global capitalism. Workers' and NGOs' frustration at the denial of freedom of association (FOA) under the CSR projects at this stage reflects well the legacy of Chinese state socialism, in particular the nature of the official trade unions and the suppressive function of the local state–global capital nexus. Therefore, the state is by no means being excluded from either business or civil society, as the orthodox view of CSR presumes.
Keywords: CSR; China; NGOs; corporate social responsibility; delegated legislation; freedom of association; labor unions; labour unions; migrant labor; migrant labour; migrant workers; nongovernmental organizations; social responsibility of business; workers’ committee

Ignorance, denial, internalisation, and transcendence: a post-structural perspective on Polanyi's double movement - Holmes, Christopher (Review of International Studies, 2013)
In this article, I suggest what an engagement between post-structuralism and the work of Karl Polanyi might look like. I do this by presenting a reading of Polanyi's concept of ‘double movement’ as a form of problematisation through binary opposition. I suggest that the central opposition that the double movement depicts – between economy and society as reflected in processes of marketisation and social protection – presents itself in such a way that the problems emanating from the opposition can only be solved through its transcendence. On one hand, the terms of transcendence are limited by the terms of the opposition. On the other hand, since transcendence is never reached, the double movement problematisation stabilises the existence of a lacuna between the lived experience of market society and the discursive field of that market society. As such, the form of the problematisation places a double-limit upon the ways in which ‘solutions’ can be presented. I present this thesis in relation to two instances of double movement discussed by Polanyi in his book, The Great Transformation. I then apply the argument to invocations of the economy-society opposition in contemporary political economic discourse, where it remains as ubiquitous as ever.
Keywords: Great Transformation, The (Book); denial (psychology); double movement; ignorance (theory of knowledge); political economic analysis; postmodernism; poststructuralism; social aspects

Rethinking ‘Embeddedness’: Law, Economy, Community - Cotterrell, Roger (Journal of Law and Society, 2013)
Ideas (of Karl Polanyi and others) that economies and markets are ‘socially embedded’ are central to recent research in economic sociology, closely paralleling socio-legal claims for studying law in ‘social context’. But the concept of embeddedness is imprecise and inadequate: a sociology of law and economy cannot rely on it but must address intellectual and moral-political concerns that its use reflects. Max Weber's writings on law and economy have inspired advocates of a new economic sociology of law, but some of Weber's key claims may be outdated, and he treats law and economy as distinct spheres rather than as facets of the social. Sociological research on law and economy should focus on ‘networks of community’ and their regulation, thus illuminating the social character of both law and economic relations. Viewing the social (including economic life) through a ‘community lens’ makes it possible to analyse cultural factors in regulating markets, while emphasizing links between economic relations and other aspects of social life.
Keywords: embeddedness

Law, Social Policy, and the Constitution of Markets and Profit Making - Veitch, Kenneth (Journal of Law and Society, 2013)
This article explores the relationship between law, society, and economy in the context of the contemporary British welfare state. Drawing on themes in Polanyi's The Great Transformation, it identifies the constitutive role of contemporary social policy and law in the creation and maintenance of markets and opportunities for the private sector in the field of welfare, focusing on the institutional mechanisms being put in place to encourage this. What emerges is a reformulation of the function of the welfare state and related law, as these are no longer predominantly driven by a logic of social protection via redistribution to those in need, but increasingly reflect the state's desire to create openings for the private sector within welfare. The institutions that once contributed to ensuring the embeddedness of the market economy in society now play an important role in processes of disembedding – with potentially detrimental consequences for those seeking assistance from the welfare state.
Keywords: Great Britain; disembeddedness; welfare state

A More Perfect Commodity: Bottled Water, Global Accumulation, and Local Contestation - Jaffee, Daniel; Newman, Soren (Rural Sociology, 2013)
Bottled water sits at the intersection of debates regarding the social and environmental effects of the commodification of nature and the ways neoliberal globalization alters the provision of public services. Utilizing Polanyi's concept of fictitious commodities and Harvey's work on accumulation by dispossession, this article traces bottled water's transformation from elite niche item to a product consumed by three fourths of U. S. households. Drawing on ethnographic research with participants in two cases of proposed spring water extraction from rural communities by industry leader Nestlé Waters, we make two principal arguments. First, the case of bottled water necessitates a reevaluation of existing theoretical frameworks regarding water privatization and commodification. Municipal tap water networks pose substantial barriers to capital accumulation, leading one influential scholar to frame water as an 'uncooperative commodity.' However, bottled water's characteristics enable it to evade many of these constraints, rendering it a 'more perfect commodity' for accumulation. Second, expansion of the market good of bottled water alters the prospects for the largely publicly provided good of tap water. We conclude that the growth of this relatively new commodity represents a more serious threat to the project of universal public drinking water provision than that posed by tap water privatization.
Keywords: HARVEY, David; bottled water; commercial products; drinking water; ethnographic analysis; fictitious commodities; globalization; households; municipal services; primitive accumulation; privatization; research

Homo Economicus and the Economics of Property Rights: History in Reverse Order - Milonakis, Dimitris; Meramveliotakis, Giorgos (Review of Radical Political Economics, 2013)
This article challenges some fundamental propositions of property rights theory by revealing the inability of new institutional economics to fully grasp the notion of property, as reflected in its narrow and problematic definition of property rights. The concept of property relations is proposed as better suited to capture the social and institutional aspects of property. By reconsidering the case of the Montagnais, originally used by Alchian and Demsetz for illustrative purposes, and drawing on the works of Polanyi and McManus, we show that the historical explanation of the emergence of (private) property rights provided by Alchian and Demsetz is flawed.JEL Codes: D02, D23, P14
Keywords: civil rights; economics; emergence; historical specificity; homo economicus; human rights; institutional economics; property; property relations; property rights; redistribution

Decommodification and Welfare State: the Case of Workplace Accident Victims - Tabin, Jean-Pierre; Probst, Isabelle; Waardenburg, George; Dransart, Dolores Angela Castelli; Pasche, Geneviève; Bolzman, Claudio (Dekommodifizierung und Wohlfahrtsstaat: der Fall von Opfern von Arbeitsunfällen., 2013)
To what extent does the social treatment of workplace injury in Switzerland enable victims to be decommodified in the sense given by Gøsta Esping-Andersen (1990) to this concept, i.e. enable them to leave the labor market in a way that allows them to uphold a socially acceptable standard of living? After a sociological discussion about the concept of decommodification, we present the results of a qualitative study conducted in Switzerland about workplace accident victims and show that the kind of index proposed by Esping-Andersen in order to compare welfare states is based on a faulty premise. (English)
Keywords: Arbeitsunfall; POLANYI, Karl, 1886-1964; Schweiz; Suisse; Switzerland; Wohlfahrtsstaat; accident du travail; accident insurance; commodification; cost & standard of living; decommodification; dekommodifizierung; démarchandisation; kommodifizierung; labor laws & legislation; labour laws & legislation; marchandisation; qualitative research; welfare state; work-related injuries; workplace accident; état social

Towards the Great Transformation: (5) Materialisms, old and new: theory, sources, and praxis (an introduction) - Catterall, Bob (City, 2013)
One of the major critical claims of this series is that the social and socio-spatial sciences, in their currently dominant form, cannot, for lack of a de-familiarising agenda, one that leads to an appropriate and continually tested strategy (praxis), effectively counter the normalized and naturalized forms and processes of late capitalist urbanization, normalized by mainstream theory in the service of established power, and their extrapolation into a ‘planetary future’. Critical urban theory presents/presented a step forward but it is losing some critical momentum and thus purchase on present and future realities in its neglect of aspects of its own intellectual heritage, of ‘extra-scientific’ resources including the cognitive aspect of the arts/humanities and ordinary experience (‘the university of the streets’), and in its too restrictive theoretical, spatial and temporal foundations.1 It thus, to a significant extent, fails to give an adequate account, a representational and ethical/normative accounting, of ‘the great transformation’ of marketisation/capitalism as told and analysed notably by Polanyi and Marx, and to the possibilities of and its relationship to praxis for a post-marketised/capitalist great transformation. We need a purposeful reading of the full range of the lived materialities of the planet (not just abstracted away into a distinctly immaterial usage of the notion of the ‘planetary’ and, indeed, of ‘urbanization’). We need in fact a sensuous materialism, an old but still unrealized project. This, the first of two futher episodes, is a brief retrospective and prospective survey, drawing on earlier work in this series and sketching in future directions, of such a materialism (materialisms, old and new): theory, sources and praxis.
Keywords: capitalism; cities & towns; cultural studies; de-familiarisation; marketisation; marketization; materialism; monsters; urban community development; urbanization

From Blue to Green and Everything in Between: Ideational Change and Left Political Economy after New Labour - Finlayson, Alan (British Journal of Politics & International Relations, 2013)
This article argues that ideational and institutionalist approaches to the study of policy continuity and change should be complemented by research into political ideologies, and with exploration of an 'intermediate' public sphere in which there is extensive intra-ideological dispute. Exploring contemporary left-wing debate about political economy in Britain it is shown that ideational change takes place in the context of disputes rooted in ideological tradition, involving the rearrangement of concepts, the emphasising of some and the marginalisation of others. In the present moment that debate is marked by what may be thought of, heuristically, as 'Keynesian', 'Polanyian', 'Schumpeterian' and 'Schumacherian' points of reference. Assessing the likelihood of this debate developing into a coherent 'crisis narrative' it is shown that the development of the relationship between these poles will be decisive but that at present they stumble over the conceptualisation of 'equality' and 'the state'.
Keywords: Great Britain; discursive and rhetorical institutionalism; economic conditions; equality; labour party; political doctrines; political economy; political ideology; politics and government; social attitudes

El Debate Moderno Sobre Los Escritos Económicos Aristotélicos - Borisonik, Hernán (The modern debate on the Aristotelian economic writings., 2013)
The present article is a critical reading of the most important modern interpretations on Aristotle's economic writings. Firstly, the debate between the “primitivists" and the “modernists" (headed by Rodbertus, Bücher and Meyer) will be studied. Then, the readings of Karl Marx, Joseph Schumpeter, Karl Polanyi and Moses Finley, will be analyzed, considering these authors as the most renowned commentators of the Aristotelian economical legacy. (English)
Keywords: ARISTOTLE; Aristóteles; FINLEY, M. I. (Moses Israel), 1912-1986; MARX, Karl, 1818-1883; SCHUMPETER, Joseph Alois, 1883-1950; economic research; economics; economía; history of economics; primitivism and modernism; primitivismo y modernismo

Los aborígenes colombianos y las paradojas del desarrollo: el caso de los emberá katíos del Alto Sinú - Martínez Triviño, Ana Milena; Reyes Albarracín, Fredy Leonardo (Colombian indigenous and the paradoxes of development: the case of the emberá katios from High Sinú., 2013)
In 1992 the construction of the Urra I hydroelectric begins, one of the most ambitious energy projects in the recent history of Colombia. Located in the inhospitable jungle region of High Sinú -northwest of the Andean territory- the environmental license granted by government entities ignored the ecological and environmental impacts the work would entail, and also failed to recognize the presence of the emberákatio indigenous people, whose constitutional rights were violated. Following the arguments presented by the economist Karl Polanyi, the article explores the environmental, social and cultural consequences caused by the energy project, in addition to delving in the strategy of violence and extermination that paramilitarism created to disrupt the organizational processes for the emberákatios, which resulted in the disappearance and murder of indigenous leaders. (English)
Keywords: aborígenes; fictitiuos merchanidise; indigenous; mercado autorregulado; mercancías ficticias; paramilitarism; paramilitarismo; self-regulated market; violence; violencia

Globalization and the Privatization of Welfare Administration in Indiana - Aman Jr., Alfred C. (Indiana Journal of Global Legal Studies, 2013)
This article explores the relationship of globalization to domestic law in the context of privatized welfare services in Indiana. It examines the ways that privatization can affect vulnerable populations such as welfare recipients by, in effect, partially dis-embedding the market from the state. It applies Karl Polanyi's conception of a double movement to illustrate how the political process can, in effect, re-embed the market in the state. Utilizing Indiana's recent experiences with welfare administration privatization, this article shows that re-embedding is not a simple question of reversing decisions already taken, but rather a complex sequencing of political and legal engagements. It recommends law reforms aimed at more easily triggering the kinds of political actions anticipated by Polanyi's analysis.
Keywords: GLOBALIZATION; INDIANA; Indiana; POLANYI, Karl, 1886-1964; POLITICAL participation laws; PRIVATIZATION; Public welfare; double movement; global legal studies; globalization; political participation laws; privatization; public welfare

The Economic-Environment Relation: Can Post-Keynesians, Regulationists and Polanyians Offer Insights? - Chester, Lynne; Paton, Joy (European Journal of Economics and Economic Policies: Intervention, 2013)
As the environmental debate has intensified, post-Keynesians, Regulationists and Polanyians remain relatively silent. All treat time as historical, consider economic issues subordinate to politics and have plenty to say about growth, institutions, uncertainty, and path-dependent events. These concepts seem pertinent to understanding the economic-environment problematic. This article explores the 'environmental potential' of these three heterodox economic traditions. We examine the conception of nature underpinning each methodological approach and the ability of their key conceptual tools to explain the economic-environment relation. Methodological pluralism and a project driven by the neoclassical agenda, we posit, seriously weakens the possibility of a post-Keynesian-grounded coherent environmental perspective. On the other hand, the Regulationists and Polanyians provide cogent analytical frameworks to advance explanations of the economic-environment relation and the contemporary environmental challenge.
Keywords: Keynesian; Keynesianism; Sraffian; capitalist systems; current heterodox approaches: institutional; economic methodology; environment and development; environment and trade; environmental accounts and accounting; environmental economics: government policy; environmental equity; evolutionary; general aggregative models: Keynes; general aggregative models: Marxian; institutional; political economy; population growth; post-Keynesian; sustainability

A Triple Movement? - Fraser, Nancy (New Left Review, 2013)
Keywords: double movement; social protection; triple movement

Insurgency and institutionalization: the Polanyian countermovement and Chinese labor politics - Friedman, Eli (Theory and Society, 2013)
Why is it that in the nearly 10 years since the Chinese central government began making symbolic and material moves towards class compromise that labor unrest has expanded greatly? In this article I reconfigure Karl Polanyi's theory of the coutermovement to account for recent developments in Chinese labor politics. Specifically, I argue that countermovements must be broken down into two constituent but intertwined "moments": the insurgent moment that consists of spontaneous resistance to the market, and the institutional moment, when class compromise is established in the economic and political spheres. In China, the transition from insurgency to institutionalization has thus far been confounded by conditions of "appropriated representation," where the only worker organizations allowed to exist are those within the state-run All China Federation of Trade Unions. However, in drawing on two case studies of strikes in capital-intensive industries in Guangdong province, I show that the relationship between insurgency and institutionalization shifted between 2007 and 2010.
Keywords: ACFTU; China; countermovement; economic capital; insurgency; labor; labour; social movements

A Critique of Economic Determinism: Karl Polanyi's Methodology. (In Russian.) - Nureev, R. M. (Zhournal Novoi Ekonomicheskoi Associacii/Journal of the New Economic Association, 2013)
Keywords: economic determinism

Karl polanyi and the economicist hybris of modernity - Polo Blanco, Jorge (Logos (Spain), 2013)
Using the work of Karl Polanyi as its axis, this study attempts to sketch a criticism of economicism and of the society that produces it, a society launched on a historical cultural path that may well be understood as a gradual economic totalization of human life. That is the critical path which will be posed here, if only in an embryonic manner.
Keywords: economic determinism; economic totalization; economicism

Nature and Power - Radkau, Joachim (Social Science History, 2013)
Nature and Power is to be understood not only as human power against nature but also as power by nature in the sense of Michel Foucault's biopouvoir (biopower) or Francis Bacon's "Naturae non imperator nisiparendo" (Only by obeying nature may we dominate nature). The fragile human attempts to get power over nature and by nature have a long history, reaching back over millennia until prehistoric times, and much of world history may be explained in part by the unstable relationship between humans and nature. The environmental approach offers afresh look at global history. The great change that has happened in modern times seems to have been described best by Karl Polanyi (1944) in his Great Transformation, which also refers to a revolution in the human relation to nature. There are primeval symbioses of humans and nature that are the basis of environmental history until modern time. A global history of the environment may be written for a long time along the three great commons of history: woodlands, water, and pasture. The dark tune of Garrett Hardin's (1968) "Tragedy of the Commons," to be sure, does not dominate the whole melody of environmental history. There is also a lot of historical evidence for Elinor Ostrom's rehabilitation of the commons. But it is better to be cautious with dogmatic theories and sweeping judgments. In modern times Hardin may be right, at least in this or that regard. Ostrom's concept applies only to local, not to global commons. The underlying philosophy of Nature and Power is neither optimism nor pessimism but possibilism.
Keywords: BACON, Francis, 1561-1626; FOUCAULT, Michel, 1926-1984; Nature & Power: A Global History of the Environment (Book); POLANYI, Karl, 1886-1964; RADKAU, Joachim; environmental history; environmentalism; nature and civilization